Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pemasaran Nasmoco di Jawa Tengah dan DIY - Saleh, Hanafi; Sudarti, Ken (Jurnal Manajemen Bisnis, 2010)
This reaserch aimed to analysed factors influencing Nasmoco’s marketing in Chentral Java and Jogjakarta. The factors were sales performance, distribution performance, service quality and promotion. Salesperson commitment, learning orientation, and motivation also tested as factorsinfluencing salesperson performance. Respondents of the study consist of Customer Representative Commission (CRC), salespersom, and supervisor. Data were collected using questionaire and analyzed using multiple regresion analysis. The result indicated that only learning orientation have no significant influence on salesperson performance, this means that Nasmoco has well aducated salesperson. The result also also showed no significant influence of promotion on sales performance. It didn’t mean that Nasmoco should leave their promotion, But Nasmoco should find creative idea in their promotion in order to get new customer and to raise customer loyalty.